Accuracy of Classification Data Mining Techniques in Business Information Systems - Literature Review in the Last Decade - Božić, Rade (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
Data mining is a concept for extraction usable information from a large set of data. It is applied in many disciplines, including the field of economics, especially at the micro level. Data mining implementation into business information systems results in informations that are key for making business decisions. In this way, potential opportunities that can provide a competitive advantages are created. How accurate are the techniques used in business information systems is a research question of this paper? The answer to this research question was introduced by a systematic literature review of the papers related to the classification techniques of data mining. Only models that are applicable in all business entities, regardless of the area of ??business, are included. The main results of the papers from the past decade are presented and interpreted.